The Effect of Using Information Systems on Employee Performance with Work Quality as an Intervening Variable at the BPJS Employment Office, Medan Raya Branch - Boris Darmo Siregar; Mesra B (Lafadz Jaya Publisher, 2023)
This research was conducted to determine the results of the influence of the use of information systems on employee performance with work quality as an intervening variable. With the type of quantitative research used, the location of this research was carried out at the BPJS Employment Medan Raya Branch Office. The research population used was 100 employees and the sample used was the entire population, namely 100 employees. The sample technique used was a saturated sample technique, the data source used was used is primary data. The results of this research are as follows: Work Quality has a positive and significant effect on Employee Performance with an original sample value of 0.409 and a P value of 0.000. Information Systems have a positive and significant effect on Employee Performance with an original sample value of 0.571 and a P value of 0.000. Information Systems have a positive and significant effect on Work Quality with an original sample value of 0.869 and a P value of 0.000.